2017
DOI: 10.1016/j.virol.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a pathogenic full-length cDNA clone of a virulent porcine epidemic diarrhea virus strain AH2012/12 in China

Abstract: Since 2010, outbreaks of variant porcine epidemic diarrhea virus (PEDV) have swept across the world causing substantial economic losses. The development of new, more effective vaccines has been hampered by difficulties in isolating strains and viral genome manipulation. In the present study, we successfully isolated a highly pathogenic field strain AH2012/12, from a pig farm reporting severe diarrhea in China. Phylogenetic analysis revealed that the new isolate belongs to group G2, which represents epidemic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…Piglets showed characteristic clinical symptoms at 12 h after inoculation and anal swab detection was positive, which indicated that virus had colonized the small intestine 12 h after challenge. This phenomenon was similar to recent infections with virulent PEDV strains (Fan et al, 2017a;Lin et al, 2015;Madson et al, 2016). The significant differences showed that virus-positive cells are present in villous epithelial cells as well as the jejunal crypt enterocytes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Piglets showed characteristic clinical symptoms at 12 h after inoculation and anal swab detection was positive, which indicated that virus had colonized the small intestine 12 h after challenge. This phenomenon was similar to recent infections with virulent PEDV strains (Fan et al, 2017a;Lin et al, 2015;Madson et al, 2016). The significant differences showed that virus-positive cells are present in villous epithelial cells as well as the jejunal crypt enterocytes.…”
Section: Discussionsupporting
confidence: 87%
“…Electron microscopy for the detection of TGEV particles was carried out as previously described (Fan et al, 2017b). Supernatants from purified TGEV JS2012-infected cell cultures showing CPEs were negatively stained with 2% ammonium molybdate, and examined with an electron microscope (Hitachi H7500, Tokyo, Japan).…”
Section: Electron Microscopymentioning
confidence: 99%
“…The pathogenicity of different PEDV subgroups has been widely investigated and many reports have confirmed that the PEDV strains of the subgroups GII-a and GII-b are highly pathogenic to suckling piglets, with infection manifesting as severe clinical symptoms with watery diarrhea, vomiting, and dehydration, high viral loads shed in the stool, severe lesions within the intestine, as evidenced by thin-transparent intestinal walls and intestinal villus atrophy or shedding, loss of bodyweight, and rapid death [19,20,29,31,32]. In the present study, PEDV strain HM2017 of subgroup GII-a was strongly virulent to suckling piglets, similar to that of the PEDV strains of subgroups GII-a and GII-b [5,33]. However, as a slight difference, 66.67% (12/18) of the experimental animals infected with strain HM2017 developed only mild diarrhea at 12 hpi, while strain HM2017 caused a significant increase in body temperature at 36 hpi with fecal shedding of high titers of viral RNA at 12 hpi and 100% mortality by 84 hpi [34].…”
Section: Discussionsupporting
confidence: 75%
“…reported that the infection titers of PEDV strain FJzz1 at passages 5, 10, and 20 had peaked from 5.44 × 10 5 to 5.71 × 10 5 TCID 50 /mL [5]. reported that the infection titer of PEDV strain AH2012/ 12 at passages 10, 20, 30, 40, and 50 ranged from 10 4.5 to 10 6.5 TCID 50 / mL [33]. reported that the viral titers of PEDV strain QIAP1401 at passages 10, 40, and 70 were 10 6.5 , 10 6.8 , and 10 7.0 TCID 50 /mL, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Beall et al constructed infectious cDNA clones of a highly pathogenic US PEDV strain PC22A using in vitro ligation of contiguous cDNA fragments, and performed in vitro transcription to generate infectious viral RNA (Beall et al, 2016). Using a similar strategy, Fan et al developed an infectious cDNA clone for a Chinese PEDV variant strain, AH2012/12 (Fan et al, 2017). Li et al developed a reverse genetics system for two Chinese PEDV strains with differing virulence by ligation of cDNA fragments into BACs one by one (Li et al, some PEDV proteins, such as S protein and ORF3, in modulating PEDV pathogenicity have been examined (Beall et al, 2016;Hou et al, 2017Hou et al, , 2019Kaewborisuth et al, 2018;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%